Unravelling the Web of Issues and Challenges in Healthcare Cybersecurity for a Secure Tomorrow - Muhd Azri Baptist, Aisyah; Abdul Halim, Farhanah; Abdillah, Siti Fatimah; Othman, Intan Waheedah; Abdullah, Nurul Jannah (Business and Economic Research, 2023)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Cybersecurity is becoming increasingly crucial specifically for healthcare organizations. The advent of digital technologies such as telemedicine, the Internet of Medical Things (IoMT), and cloud-based solutions has brought about transformative advancements in patient care and administrative processes. However, with this progress comes an array of cyber threats that can have adversarial consequences if managed ineffectively. Driven by the growing concerns within the realm of cybersecurity, this paper delves into the issues and challenges faced by healthcare organizations in the deployment of cyber technologies. The research aims to dissect the multifaceted issues and challenges that contribute to compromised cybersecurity measures, resulting in potential data and system breaches. The study seeks to offer valuable insights, thereby paving the way for informed strategies and solutions to enhance cyber defenses and mitigate risks of unauthorized access and data breaches.